Learning in the Real Place. (February 2015) - Han, Heeyoung; Roberts, Nicole K.; Korte, Russell
<x xml:space="preserve">Abstract</x> Purpose To understand medical students' learning experiences in clerkships: learning expectations (what they expect to learn), learning process (how they learn), and learning outcomes (what they learn). Method Using a longitudinal qualitative research design, the authors followed the experiences of 12 participants across their clerkship year (2011–2012) at the Southern Illinois University School of Medicine. Interview data from each participant were collected at three points (preclerkship, midclerkship, and postclerkship) and analyzed using a grounded theory approach. Additionally, the authors observed participants through a full clerkship day to augment the interviews. Results Before clerkships, students expected to have more hands-on experiences and become more knowledgeable by translating textbook knowledge to real patients and practicing diagnostic thinking. During clerkships, students experienced ambiguity and subjectivity of attending physicians' expectations and evaluation criteria. They perceived that impression management was important to ensure that they received learning opportunities and good evaluations. After clerkships, students perceived that their confidence increased in navigating the health care environments and interacting with patients, attendings, and residents. However, they felt that there were limited opportunities to practice diagnostic thinking. Students could not clearly discern the decision-making processes used by attending physicians. Although they saw many patients, they perceived that their learning was at the surface level. Conclusions Students' experiential learning in clerkships occurred through impression management as a function of dynamic social and reciprocal relationships between students and attendings or residents. Students reported that they did not learn comprehensive clinical reasoning skills to the degree they expected in clerkships.